Role of Microorganisms in Climate Change - Hadiza Umar, Tafida; Jibrin Ndejiko, Mohammed; Mohammed Abdullahi; Abdullahi Asmau (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
Global warming and accompanying climate change are some of the serious problems in the world due to increase in the concentration of greenhouse gases that have been the major cause of this problem. Though anthropogenic emissions from the burning of fossil fuels and industrialization have long been identified as the sources of these gases. However, microorganisms contribute significantly to the generation of greenhouse gases in the atmosphere and also removal of these gases from the atmosphere. Thus, this review brings to light the role microorganisms play in the emission of greenhouse gases into the atmosphere from different sources including terrestrial soils, carbon cycle, agricultural lands, ruminants, landfills, wetlands and marine microorganisms. This work also takes a look at the microbial response to climate change as well as microbial-related strategies that can be used to mitigate climate change. A good understanding of these microbial processes and strategies holds a huge potential for utilizing and manipulating microorganisms to mitigate climate change through the reduction of greenhouse gasses released from the ecosystem.